ADAPTASI SUHU TUBUH TERHADAP LATIHAN DAN EFEK CEDERA DI CUACA PANAS DAN DINGIN - Satia Graha, Ali (Jorpres (Jurnal Olahraga Prestasi), 2010)
Somebody's skill to adapt in their different surrounding environment is differing from one to another; it can be seen in the level of the acclimatization toward the temperature. Today, we have to do our activities or practices in a high temperature, we will lose many body's liquid. From that reason, body will do some of physiologic mechanism to send the heat out and stabilized the body temperature by paying attention and doing efforts to change the body liquid which was out and bring the body's mineral internally pr externally.Some of injuries which can happen when we do some practices in dry area are heat cramps, heat syncope, heat exhaustion (there are two types: water completing, salt completing), and heat stroke. Many sweats out from the body can cause dehydration.In the other hand, if we doing some practicing in cold area, the body physiology adaptation is side system velocity decrease, the body will decrease blood pale velocity on the extremity in skin surface. Body's chill setting is an increasing metabolic rapid caused by thyroxin and catecholamine release (epinephrine and nor epinephrine)  Keywords: body's temperature, practice, injury effect, hot and cold weather